2005
DOI: 10.5194/acpd-5-7457-2005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the observation of mesospheric air inside the arctic stratospheric polar vortex in early 2003

Abstract: Abstract. During several balloon flights inside the Arctic polar vortex in early 2003, unusual trace gas distributions were observed, which indicate a strong influence of mesospheric air in the stratosphere. The tuneable diode laser (TDL) instrument SPIRALE (Spectroscopie InFrarouge par Absorption de Lasers Embarqués) measured unusually high CO values (up to 600 ppb) on 27 January at about 30 km altitude. The cryosampler BONBON sampled air masses with very high molecular Hydrogen, extremely low SF6 and enhance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 20 publications
8
42
1
Order By: Relevance
“…SPIRALE measurements therefore extend the correlation values to lower N 2 O values thanks to the large mesospheric descent observed by the SPIRALE measurements. This mesospheric descent has also been observed on March 2003 by other instruments [ Engel et al , 2005].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…SPIRALE measurements therefore extend the correlation values to lower N 2 O values thanks to the large mesospheric descent observed by the SPIRALE measurements. This mesospheric descent has also been observed on March 2003 by other instruments [ Engel et al , 2005].…”
Section: Discussionsupporting
confidence: 79%
“…Above 23 km, the measurements show a very intense mesospheric descent compared to those referred to by Plumb et al [2002] because the mixing ratio of CO observed is as large as 600 ppbv. This large mesospheric descent has also been observed later, in March 2003 [ Engel et al , 2005]. Measurements allow us to determine new CH 4 :N 2 O correlation values.…”
Section: Resultssupporting
confidence: 57%
“…Here we analyze ozone‐tracer relations in the Arctic winter 2002/2003, when an intrusion of mesospheric air into the stratosphere was observed [ Engel et al , 2006; Huret et al , 2006]. (Note that the term “intrusion” is used here in a different sense than quasi‐isentropic filamentary intrusions into the vortex from the extratropics, a concept that frequently also appears in the literature.)…”
Section: Introductionmentioning
confidence: 99%
“…The mesospheric intrusion may be identified as strongly enhanced CO mixing ratios. It occurred in the Arctic vortex in early 2003 in a layer descending from ∼30 km in late January to ∼25 km by early March [ Engel et al , 2006; Huret et al , 2006]. This mesospheric air was sampled again in the vortex in late March [ Engel et al , 2006; Wetzel et al , 2006].…”
Section: Introductionmentioning
confidence: 99%
“… de Zafra and Muscari [2004] measured CO column densities that regularly reached above 10 17 cm −2 , in good agreement with Solomon et al 's [1985] predictions. Recently, interest in upper‐atmospheric CO has increased, with both satellites and ground‐based instruments used to monitor concentrations [e.g., Dupuy et al , 2004; Filipiak et al , 2005; Engel et al , 2005; Jin et al , 2005; Velazco et al , 2007].…”
Section: Introductionmentioning
confidence: 99%